Pengaruh Likuiditas, Leverage dan Ukuran Perusahaan Terhadap Agresivitas Pajak Sektor Properti, Real Estate Dan Konstruksi Bangunan - Asih Purwana Sari; Ary Prasetyo; Ita Mustika (Jurnal Mirai Management, 2023)
This research aims to determine the influence of the independent variables profitability (X_1), leverage (X_2) and company size (X_3) on the dependent variable tax aggressiveness (Y). The method used in this research is quantitative using secondary data from the BEI for 2017-2021. The sampling method uses purposive sampling technique. Purposive sampling is a technique for determining samples from the population with certain considerations with a sample size of 55 companies from the population of companies in the property, real estate and building construction sectors which in 2017-2021 were registered on the IDX. The analysis used in this research is a regression equation model with SPSS version 23 software. The results of this research include: partially, the independent variable profitability (X_1) has a significant negative effect on the dependent variable tax aggressiveness (Y). Partially, the independent variable leverage (X_2) has an insignificant negative effect on the dependent variable tax aggressiveness (Y). Partially, the independent variable company size (X_3) has a significant positive effect on the dependent variable tax aggressiveness (Y). Apart from that, simultaneously the independent variables profitability (X_1), leverage (X_2) and company size (X_3) have a significant effect on the dependent variable tax aggressiveness (Y). Keywords: profitability, leverage, company size, tax aggressiveness, SPSS